2013
DOI: 10.1111/jon.12019
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Asymmetry, and Age Influence on Dynamic Cerebral Autoregulation Measured by Spontaneous Fluctuations of Blood Pressure and Cerebral Blood Flow Velocities in Healthy Individuals

Abstract: Background Cerebral autoregulation (CA) enables the brain to maintain stable cerebral blood flow (CBF). CA can be assessed non-invasively by determining correlations between cerebral blood flow velocity (CBFV) and spontaneous changes in blood pressure. Post-recording signal analysis methods have included both frequency- and time-domain methods. However, the test-retest reliability, cross-validation, and determination of normal values have not been adequately established. Methods In 53 healthy volunteers a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 25 publications
3
29
1
Order By: Relevance
“…Further, the main purpose of including the control group was to compare postural changes in Mx and not for direct comparison of absolute values in the two groups. In addition, The Mx value is known to vary to some extent as a study by Ortega-Gutierez et al (2014) found variations between healthy subjects of similar magnitudes as ours [ 35 ].…”
Section: Discussionsupporting
confidence: 52%
“…Further, the main purpose of including the control group was to compare postural changes in Mx and not for direct comparison of absolute values in the two groups. In addition, The Mx value is known to vary to some extent as a study by Ortega-Gutierez et al (2014) found variations between healthy subjects of similar magnitudes as ours [ 35 ].…”
Section: Discussionsupporting
confidence: 52%
“…In this study, investigators found that changes in TCD were similar in patients with LVADs and controls arguing against the loss of cerebral auto-regulation [27•]. Other more advanced measures of cerebral auto-regulation, such as direct cerebral auto-regulation with a hypotensive or post-occlusive hyperemic challenge [28], have not been established in this patient population. Lastly, little data is known on whether arteriolar degenerative processes, such as accumulation of αβ-amyloid in cerebral amyloid angiopathy among those older than 55, interacts with blood pressure to increase the risk of ischemic or hemorrhagic stroke as it does in non-LVAD patients [29].…”
Section: Hypertension and Stroke In Left Ventricular Assist Devicesmentioning
confidence: 92%
“…Transcranial Doppler ultrasongraphy combined with continuous blood pressure monitoring were used to evaluate DCA, as has been described previously [31,33]. Briefly, cerebral blood flow velocities (CBFV) were assessed using TCD (DWL-Multidop-X, Sipplingen, Germany).…”
Section: Methodsmentioning
confidence: 99%